MICROBIOLOGICAL ASSESSMENT OF WATER QUALITY OF LAKE KOTOKELSKOE AND METHOD OF ITS PURIFICATION - D. D. Tsyrenova; D. D. Barkhutova; V. P. Garankina; B. B. Namsarayev (Acta Biomedica Scientifica)
During assessment of water quality in the lake Kotokelskoe, we observed some cyanobacteria that forming harmful to human and animal toxins. According to the chlorophyll a content, the lake Kotokelskoe is eutrophic with high productivity of phytoplankton. But microbiological parameters such as total number of microorganisms and saprophytes cause to classify this lake as «polluted waters». Preparation. «Baikal EM 1» is actively involved to the processes of self-purification of water. It could provide decreasing of chlorophyll content total number of microorganisms in aquarium water.